Carbon storage in arbor forests under the background of carbon neutrality (Bangladesh Journal of Botany, 2023)
Arbor are the main body of forest plants and have the role and status of "skeleton" of carbon storage. In the present study a large number of arbor forest carbon storage literature and the research progress of arbor forest carbon storage were reviewed. Results showed that the carbon storage of pine trees in arbor forest was relatively high; the areas with large carbon storage in arbor forest were Tibet, Yunnan, Heilongjiang, Sichuan, Inner Mongolia and Jilin.The carbon storage of arbor forests of different age groups increases with stand age and arbor forests of different origins have higher carbon stocks than planted forests in natural forests.Bangladesh J. Bot. 52(2): 695-699, 2023 (June) Special